2007
DOI: 10.1177/000348940711600709
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Investigation and Mechanism of Air-Bone Gaps in Large Vestibular Aqueduct Syndrome

Abstract: Objectives-Patients with large vestibular aqueduct syndrome (LVAS) often demonstrate an airbone gap at the low frequencies on audiometric testing. The mechanism causing such a gap has not been well elucidated. We investigated middle ear sound transmission in patients with LVAS, and present a hypothesis to explain the air-bone gap.Methods-Observations were made on 8 ears from 5 individuals with LVAS. The diagnosis of LVAS was made by computed tomography in all cases. Investigations included standard audiometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0
8

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(122 citation statements)
references
References 24 publications
(73 reference statements)
4
110
0
8
Order By: Relevance
“…It should be noted that the pressure decrease due to the VA was observed at low frequencies (below about 1 kHz). This is consistent with the previous studies [4,5]. Those studies showed that the VA or the semicircular canal dehiscence can be a TW and that the sound energy is shunted through the TW at low frequencies in AC.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It should be noted that the pressure decrease due to the VA was observed at low frequencies (below about 1 kHz). This is consistent with the previous studies [4,5]. Those studies showed that the VA or the semicircular canal dehiscence can be a TW and that the sound energy is shunted through the TW at low frequencies in AC.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, a third window (TW), which is another fluid pathway in the cochlea except the OW and RW, was suggested as a possibile factor to explain the asymmetry of the volume velocity ratio. However, in spite of many studies for potential TWs [1,4,5], it is still unclear which opening in the real cochlea acts as the TW causing the asymmetry of the ratio. In order to further investigate the effect of the TWs on the asymmetry of the volume velocity ratio, we used a 3-D finite-element (FE) human-ear model consisting of the middle ear and the cochlea.…”
Section: Introductionmentioning
confidence: 99%
“…These patients often present with a mixed hearing loss. The lack of pathologic findings in the middle ear in these patients has been shown by a number of studies using tests such as tympanometry, acoustic reflexes, laser Doppler vibrometry, air-conducted VEMP and OAE testing, and middle ear explorations (30). The enlarged vestibular aqueduct probably provides a pathologically large communication between the bony vestibule and the cranial cavity, resulting in an air-bone gap, similar to that observed in SCD.…”
Section: Large Vestibular Aqueduct Syndromementioning
confidence: 68%
“…For example, patients with SCD may exhibit sound-and/or pressure-induced vertigo or demonstrate low thresholds for air-conducted vestibular evoked myogenic potential (VEMP) responses (10,11,29). Similarly, patients with an enlarged vestibular aqueduct may have low thresholds on air-conducted VEMP testing (30). It is not known why some individuals with third-window lesions have solely auditory or vestibular manifestations, whereas others have both.…”
Section: Mechanism Of Conductive Hearing Lossmentioning
confidence: 99%
See 1 more Smart Citation